General expression of poly(methyl methacrylate) optical fiber Bragg grating sensing response - Zhang, Wei; Webb, D. J. (IEEE, 2018)
Poly(methyl methacrylate) (PMMA) optical fiber inherently responds to the changes of temperature and relative humidity. PMMA optical fiber Bragg grating (POFBG) has been reported with diverse temperature and relative humidity sensitivities. These results cannot present the full performance of a POFBG sensor, as they are measured at limited environmental conditions. In this letter, we systematically investigated the POFBG temperature and relative humidity sensing responses. We found that POFBG temperature/relative humidity sensitivity is the function of both temperature and relative humidity. In the experiments, POFBG sensing responses vary linearly with temperature/relative humidity at fixed relative humidity/temperature. Based on this linearity, a general expression of POFBG sensing response to temperature and relative humidity has been obtained and verified for the first time to describe the POFBG performance in the desired operation range. The anisotropy in POF induced by drawing history could induce uncertainty in POFBG response but pre-straining POFBG overcomes this problem.
Keywords: Fiber Bragg gratings; polymer optical fiber; temperature measurement; relative humidity measurement